Comparing landscape and infrastructural heterogeneity within and between ecosystems - Boone, Randall B.; BurnSilver, S.B.; Kruska, R.S. (Springer, 2008)
Ecological research throughout much of the last century focused upon manipulative experiments on areas of a few square meters or less (Kareiva and Andersen 1988). The last quarter of the century saw the development of landscape ecology and the emergence of macroecology as a bonafide method of research and discovery (e.g., Brown 1995, Blackburn and Gaston 2002). Geographical and human-ecological research increasingly has successfully integrated human populations and their behaviors into analyses of land use change (Rindfuss and Stern 1998). Today, readily available broad-scale data, such as satellite images and global spatial databases, make comparing attributes of landscapes and the people who inhabit them uniform, thorough, repeatable, and relatively inexpensive (Roughgarden et al. 1991).